2017
DOI: 10.1096/fj.201601237
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulated miR‐26a promotes proliferation, migration, and invasion via negative regulation of MTDH in esophageal squamous cell carcinoma

Abstract: Numerous studies have reported that the role played by miR-26a in cancer is controversial, but whether miR-26a regulates metadherin (MTDH) expression in esophageal squamous cell carcinoma (ESCC) is unclear. We performed this study to investigate the clinical relevance of miR-26a expression in ESCC. miR-26a was detected by using the hybridization method. To functionally analyze the role of miR-26a in ESCC cell lines, KYSE-450 and Eca109 cells were employed, whose endogenous miR-26a was artificially down- or up-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…MiR‐26a has been implicated in multiple biological processes, such as proliferation, invasion, differentiation, angiogenesis and energy metabolism in cancer cells . It has been reported that inhibition of miR‐26a contributes to proliferation, migration and invasion via targeting metadherin in oesophageal squamous cell carcinoma .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR‐26a has been implicated in multiple biological processes, such as proliferation, invasion, differentiation, angiogenesis and energy metabolism in cancer cells . It has been reported that inhibition of miR‐26a contributes to proliferation, migration and invasion via targeting metadherin in oesophageal squamous cell carcinoma .…”
Section: Discussionmentioning
confidence: 99%
“…26 It has been reported that inhibition of miR-26a contributes to proliferation, migration and invasion via targeting metadherin in oesophageal squamous cell carcinoma. 27 Overexpression of miR-26a reduced tumour cell growth of osteosarcoma in vitro and in vivo. 28 In ovarian cancer cells, reinforced expression of miR-26a inhibited proliferation and induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…miR-26a-5p promoted chicken follicular theca cell proliferation and significantly up-regulated the expression of the anti-apoptotic BCL2 gene to inhibit apoptosis by targeting a trinucleotide repeat containing 6A gene (Kang et al, 2017). In addition, miR-26a also participates in regulating proliferation, apoptosis, migration, autophagy and invasion in multiple types of cancer cells, including vascular smooth muscle cells (Tan, Yang, Liu, & Yan, 2017), hepatocellular carcinoma cells (Jin et al, 2017;Li, Ren, et al, 2017), oesophageal squamous cell carcinoma cells Yang et al, 2017) and gastric cancer cells (Ding et al, 2017), (Correia et al, 2015;Kvansakul & Hinds, 2013;Mignard, Lalier, Paris, & Vallette, 2014;Volkmann, Marassi, Newmeyer, & Hanein, 2014). The anti-apoptotic proteins are located in the cytosol and are associated with the mitochondrial outer membrane, while the pro-apoptotic effector proteins are the mediators of mitochondrial outer membrane permeabilization (Correia et al, 2015;Mignard et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…miR‐26a‐5p promoted chicken follicular theca cell proliferation and significantly up‐regulated the expression of the anti‐apoptotic BCL2 gene to inhibit apoptosis by targeting a trinucleotide repeat containing 6A gene (Kang et al, ). In addition, miR‐26a also participates in regulating proliferation, apoptosis, migration, autophagy and invasion in multiple types of cancer cells, including vascular smooth muscle cells (Tan, Yang, Liu, & Yan, ), hepatocellular carcinoma cells (Jin et al, ; Li, Ren, et al, ), oesophageal squamous cell carcinoma cells (Li, Liang, et al, ; Yang et al, ) and gastric cancer cells (Ding et al, ), by targeting different genes. In this study, miR‐26a overexpression arrested cells in G0/G1 phase, inhibited proliferation and promoted swine Sertoli cells apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation